A cross-border educational session promoting nursing dysphagia screening in Greece: A pilot study - Mandysová, Petra; Fusek, Josef; Tsiou, Chrysoula; Plakas, Sotirios (My University, 2016)
Aim: Dysphagia is a common and potentially serious problem in patients with neurological conditions. In many countries, dysphagia screening is used, which contributes to better patient outcomes. In Greece, the implementation of dysphagia screening has not yet been described. The aim was to examine the effectiveness of an educational session delivered to Greek masters-level nursing students and their faculty on the correct use of an 8-item nursing dysphagia screening instrument developed in the Czech Republic. Methods: Fifteen students and nursing faculty members of the Technological Educational Institute of Athens were enrolled in this descriptive pilot study. They were educated on dysphagia in a session consisting of a theoretical and practical part and a discussion. The participants were asked to indicate their clinical experience with dysphagia and their opinion on the importance of nurses’ involvement in dysphagia assessment. Their knowledge of the screening procedure and interpretation and documentation of the result was tested using a hypothetical patient case. Results: In this study, 4 (27%) participants had prior experience with patients with dysphagia. All of them thought that nurses’ involvement in dysphagia assessment was very important. Slightly more than half of the participants identified, interpreted, and documented all of the 8 item results correctly. Conclusion: The participants were motivated to learn, however, complete mastery of the assessment technique was not achieved. The learning experience was affected by several issues that were unique to Greece, and the participants’ efforts focused on understanding how the new knowledge and skills could affect their daily practice. Direct ongoing support in the clinical setting could be beneficial.
Mezinárodní edukační lekce propagující screening dysfagie sestrou v Řecku: pilotní studie
Keywords: Brief Bedside Dysphagia Screening Test-Revised; Greece; Nursing education; Assessment skills; Neurological conditions; Brief Bedside Dysphagia Screening Test-Revised; Řecko; edukace v ošetřovatelství; vyšetřovací dovednosti; neurologická onemocnění